Efektifitas Supervisi Kepala Madrasah dalam Upaya Peningkatan Kinerja Guru - A. Tsabat Izzudin; Sri Susilowardani (Journal on Education, 2023)
To carry out its duties and responsibilities, a teacher is required to have several abilities and skills, which are shown in the form of a teacher's performance. It's just that not all teachers have good performance qualities, so it is necessary to make various kinds of efforts to improve the performance of these teachers. The purpose of this research is to find out efforts to improve teacher performance through the supervision of the principal. This research is a type of action research, which is carried out in 2 research cycles, namely, cycle I and cycle II. In each cycle, there are stages of planning, action, observation and evaluation, and reflection. The subjects involved in this study were 10 people, consisting of 12 teachers and 1 administrative employee. Data collection in the study was carried out using observation, interviews, documentation, and questionnaires. The research data were then analyzed using descriptive statistical analysis techniques, namely by looking for the average teacher performance improvement which was then converted into a fivescale PAP to determine the teacher's high performance after supervision by the principal. The results showed that there was an increase in teacher performance in each cycle where at the pre-cycle stage the average performance appraisal only reached 75%, then increased in the first cycle to 90%, and increased again in the second cycle to 100%, where all teachers have had a good performance. the good one. So based on these results it can be concluded that the principal's supervision can significantly improve teacher performance.